Bureaucratic Reform and Economic Growth: The Case of Bintan Regency's Development Strategy - Ibaniyah, Ibaniyah; Metyana, Irma; Sintiana, Ranti Marshanda; Dewi, Sri Kesuma; Ramadan, Syafiq (Journal Governance Bureaucratic Review, 2024)
Bureaucratic reform is a critical driver of economic growth, especially in decentralized regions where local governance quality directly affects development outcomes. This study investigates the impact of bureaucratic reform on the economic performance of Bintan Regency, Indonesia. Using a qualitative case study approach that includes document analysis and systematic literature review, the research explores how administrative modernization contributes to improved service delivery, investment facilitation, and institutional efficiency. Findings reveal that reform initiatives particularly digital licensing systems, streamlined bureaucratic processes, and enhanced inter-agency coordination have significantly supported economic growth. In 2023, Bintan recorded a 6.14% GRDP growth, with the manufacturing sector contributing 40.25% and capital formation accounting for 59.99% of the growth from the expenditure side. These outcomes align with meta-analytic evidence that highlights the positive effects of bureaucratic transparency and performance-based governance on regional development. However, challenges such as political clientelism and institutional fragmentation remain barriers to sustained reform. The study concludes that while Bintan's reforms have yielded tangible economic benefits, long-term success depends on embedding reform into legal and operational structures, ensuring resilience against political disruptions. This case provides practical insights for policymakers seeking to align governance innovation with inclusive economic development. The research highlights the importance of adaptive bureaucratic structures in achieving inclusive economic growth, suggesting that Bintan’s experience can serve as a model for other regions facing similar governance challenges.